An ab initio conformational study on captopril - Zamarbide, Graciela Nidia (2003)
Captopril can interact regio- and stereo-specifically with various functional groups present at the active site of angiotensin converting enzyme (ACE). Since no X-ray structure of ACE is available, Captopril, as an ACE inhibitor may be used as a 'molecular caliper', to estimate upper and lower bound values for separation d, where the mercaptidic terminal group of the molecule is linked to the enzyme Zn2+ cofactor, while the carboxylate links via an hydrogen bond to the guanidine moiety of an arginine side chain. As the results of this Ab Initio study, the conformations of the dianionic form of the full captopril molecule are reported here.